Symmetric telepresence using robotic humanoid surrogates. (29th April 2015) - Nagendran, Arjun; Steed, Anthony; Kelly, Brian; Pan, Ye
Abstract: Telepresence involves the use of virtual reality technology to facilitate apparent physical participation in distant events, including potentially performing tasks, while creating a sense of being in that location. Traditionally, such systems are asymmetric in nature where only one side (participant) is "teleported" to the remote location. In this manuscript, the authors explore the possibility of symmetric three‐dimensional telepresence where both sides (participants) are "teleported" simultaneously to each other's location; the overarching concept of symmetric telepresence in virtual environments is extended to telepresence robots in physical environments. Two identical physical humanoid robots located in UK and the USA serve as surrogates while performing a transcontinental shared collaborative task. The actions of these surrogate robots are driven by capturing the intent of the participants controlling them in either location. Participants could communicate verbally but could not see the other person or the remote location while performing the task. The effectiveness of gesturing along with other observations during this preliminary experiment is presented. Results reveal that the symmetric robotic telepresence allowed participants to use and understand gestures in cases where they would otherwise have to describe their actions verbally. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this manuscript, the authors explore the possibility of symmetric three‐dimensional telepresence where both sides (participants) are "teleported" simultaneously to each other's location; the overarching concept of symmetric telepresence in virtual environments is extended to telepresence robots in physical environments. Results reveal that the symmetric robotic telepresence allowed participants to use and understand gestures in cases where they would otherwise have to describe their actions verbally.